2005
DOI: 10.1080/02640410400021310
|View full text |Cite
|
Sign up to set email alerts
|

The relative age effect in youth soccer across Europe

Abstract: The potential asymmetries in the birth-date distributions of youth soccer players across ten European countries (2175 age citations) were considered. First, we examined the birth-dates of players representing national youth teams in international competitions. Second, the birth-dates of players representing professional club teams in international youth tournaments were analysed. Kolmogorov-Smirnov tests were used to assess differences between observed and expected birth-date distributions. Regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
427
8
58

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 460 publications
(531 citation statements)
references
References 35 publications
38
427
8
58
Order By: Relevance
“…Generally, players born on the last months of the year have more chances to show a less advanced maturity state than those born on the beginning of the year [5][6] . Some studies demonstrate di erences on the players' physical capacities of those born in di erent periods of the year, since besides being larger and having higher body mass, older players present better results on velocity and agility tests 10,23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, players born on the last months of the year have more chances to show a less advanced maturity state than those born on the beginning of the year [5][6] . Some studies demonstrate di erences on the players' physical capacities of those born in di erent periods of the year, since besides being larger and having higher body mass, older players present better results on velocity and agility tests 10,23 .…”
Section: Discussionmentioning
confidence: 99%
“…It happens because younger athletes are stimulated to nd solutions to the constrains imposed by the game through tactical dimensions rather than physical advantages 6 . ese results showed that there are particularities between di erent youth categories when compared with similar study carried out by T et al 3 , wich evaluated players between 13 to 18 years of age, related to the in uence of the tactical principles, since there were di erent principles that showed higher in uence on the development in each category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Helsen et al (2000), Helsen et al (2005) and Edgar and O'Donoghue (2005) find the RAE in competitive sports that involve young athletes and especially in soccer it is a well documented phenomenon (Barnsley et al, 1992;Mujika et al, 2009;Vaeyens et al, 2005). Musch and Grondin (2001) However, a more detailed analysis, as provided in Figure 2, does show empirical evidence for the RAE in American football.…”
Section: The Relative Age Effectmentioning
confidence: 99%